Engineering Education Experience, E3, for teachers: a professional development workshop for 6-12 engineering education - Grauer, Bette; Roberts, Karen L.; Roberts, Thomas C.; Clark, Gary A.; Betz, Amy Rachel (My University, 2013)
This paper describes a professional development program developed for middle and high school teachers, counselors, and administrators designed to provide information about grades 6–12 engineering curricula, engineering career paths, the Kansas State University College of Engineering, and student preparation for the study of engineering. The program, Engineering Education Experience (E3) was developed at Kansas State University, a midwestern university with a comprehensive engineering college. The program was created to support the University Engineering Initiative Act (UEIA). The UEIA, approved by the Kansas Legislature in 2011, provides funding for the state’s three engineering colleges to increase the number of engineering graduates in the state. In support of this plan, Kansas State University College of Engineering created E3 to inform 6–12 teachers, administrators and counselors of engineering as a topic of study and career path with the intent of reaching middle and high school students. The program was offered to teachers as a summer professional development workshop. During the summer of 2012, the Kansas State University College of Engineering hosted two 3- day engineering education workshops for teachers. Topics of lessons and activities included (a) engineering design, (b) problem-solving, (c) biological and environmental engineering, (d) nanomaterials, and (e) wind power. Activities and discussions allowed teachers to extend their knowledge of STEM topics and to meet with College of Engineering administrators, faculty, and students. Sixty-six teachers, counselors, and administrators participated in the E3 workshops. Participants included middle and high school math, physical science, biological science, and gifted teachers, along with counselors and administrators. Participants received 20 hours of professional development credit. A pre-workshop survey assessed their existing knowledge of engineering and what they hoped to learn from the workshop. Participants also completed a post workshop evaluation survey. A majority of the responses were favorable to the E3 workshop, with 98.5% of participants rating overall quality of the presenters/sessions as very good or excellent. Participants indicated satisfaction in presentations of the many areas and applications of engineering, variety of programs, and careers associated with engineering, and engineeringrelated activities for the classroom. This paper includes discussion topics and lesson plans developed for the E3 program and used during the workshop, including hands on and collaborative activities related to biological and environmental engineering, nanomaterials, and wind power.
Keywords: Engineering education; Professional development; Kansas State University; Workshop; Middle school teachers; High school teachers